Videocolonoscopy and chromoscopy in diagnostics of flat adenomas of the large intestine (Prospective study) - S. I. Zaikin; V. V. Agadzhanyan; T. V. Levchenko; Ye. A. Pervov; P. A. Frolov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate frequency of flat adenomas of the large intestine in men and women of various age groups, that underwent total videocolonoscopy. To study macroscopic and morphological differences of flat adenomas in relation to locating within the large intestine.Materials and methods. Total colonoscopy by CF-V70L device («Olympus», Japan) after preparation by Fortrans (macrogoal) «Ipsen» company (France) was carried out in 1859 patients, inhabitants of Kuzbass region. Each patient with suspicion to structural mucosal changes underwent guided chromoscopy with 0,2% indigo carmine solution. Neoplasms, which were revealed, were subjected to biopsy by FB-24U forcipes or resection by SD-17U loop («Olympus», Japan). Results. Overall 1859 patients were investigated, in 849 cases (45,7%) 1631 adenoma has been found, 1344 (82,5%) of them were of the I type. At 176 (9,5%) patients 287 (17,5%) adenomas II of type were revealed. Flat adenomas were found most often in males in the age of 30 to 49 years at the right part of the colon, 285 (99,3%) adenomas were of the IIa type, 270 (94,1%) were <10 mm in size. The majority of flat adenomas – 275 (95,8%) – had tubular structure, in 14 (4,9%) the high degree dysplasia was found. Conclusions. Flat adenomas of the large intestine – is not an infrequent disease among Kemerovo region inhabitants (it is found in 9,5 % of the patients undergoing total videocolonoscopy with chromoscopy). The risk of neoplastic transformation increases with increase of><10 mm in size. The majority of flat adenomas – 275 (95,8%) – had tubular structure, in 14 (4,9%) the high degree dysplasia was found.Conclusions. Flat adenomas of the large intestine – is not an infrequent disease among Kemerovo region inhabitants (it is found in 9,5 % of the patients undergoing total videocolonoscopy with chromoscopy). The risk of neoplastic transformation increases with increase of the flat adenoma size, at the presence of central excavation and location in right part of the colon.